Analysis of Early Warning System (EWS) and Risk-Based Capital (RBC) on the Financial Performance of Sharia Insurance Companies - Rofi Atun Darojad; Rais Sani Muharrami (Universitas Al-Qolam Malang, 2026)
Maintaining financial performance and public trust is a difficulty for the Islamic insurance sector, especially in light of many company default situations. When evaluating how well Islamic insurance businesses manage tabarru' funds, underwriting surplus is a crucial metric. The purpose of this study is to examine the impact of Risk-Based Capital (RBC) and the Early Warning System (EWS), as represented by the claim expense, retention, and asset liquidity ratios, on the underwriting surplus of Islamic general insurance companies that are registered with the Indonesian Islamic Insurance Association (AASI) for the years 2022–2024. Quarterly data from six Islamic general insurance businesses, three full-fledged general insurance companies and three Islamic unit insurance companies. The study employs a quantitative methodology. The study's findings show that underwriting surplus is unaffected by the retention ratio or the claim expense ratio. On the other hand, underwriting excess is influenced by the asset liquidity ratio and Risk-Based Capital (RBC). All factors have a substantial impact on underwriting surplus at the same time.